An Analysis of Pronunciation of the Nasal Sound /n/ Followed by the Bilabial Nasal Consonant /m/ at Indonesian Japanese Learners - Rike Febriyanti; Nurica Virdaus (Chi'e: Journal of Japanese Learning and Teaching, 2022)
The purpose of this study was to find out how the pronunciation of the nasal sound /ɴ/was followed by the nasal bilabial consonant /m/ by Indonesian Japanese learners. This study uses a descriptive qualitative approach. This research data is in the form of audio recordings of 13 students learning Japanese at Brawijaya University, which is compared with the pronunciation of the same sentence in the Suzuki-kun feature in OJAD. The analysis results found sound assimilation (on'in datsuraku), so the nasal sound produced in the middle of the vocabulary was the nasal bilabial /m/. The presence of sound assimilation causes the duration when pronouncing the nasal bilabial /m/to be quite long, with a duration range of /m/ 0.121208 – 0.161208 seconds. The nasal sound is produced if it is seen from the presence or absence of the insertion of /ɴ/. The duration, it is found in the pronunciation of [kammoɴ] and [semmenʑo], respectively, that 3 out of 13 students agree with the pronunciation of OJAD, while in the pronunciation of [ kiɕokɯmammeɴ], only 1 in 13 students qualified. So it can be said that students still tend to pronounce the nasal sound /ɴ/ followed by the nasal bilabial sound /m/ with a nasal sound other than the bilabial /m/. Keywords : Jurnal Pendidikan Bahasa Jepang Japanese Education JournalJapanese Nasal SoundBilabial Nasal ConsonantJapanese Language Education